PECULIARITIES OF TEACHING ENDOCRINOLOGY IN THE CONDITIONS OF RUSSIAN-UKRAINIAN AGGRESSION - Скрипник, Надія; Артеменко, Наталія; Човганюк, Ольга; Костіцька, Ірина; Василечко, Мар’яна; Дідушко, Олена; Чернявська, Ірина; Боцюрко, Володимир; Оринчак, Марія (SWorldJournal, 2024)
In the face of Russian aggression against Ukraine, Ivano-Frankivsk National Medical University prioritizes teaching the discipline of "Endocrinology" with a focus on preparing students for emergency situations, resource scarcity, and identifying effectiv